Transformation of APHP SMK Baitul Izza Students from the Classroom to the Industrial World - Wihardana Jannati; Didik Nurhadi; Yoto Yoto (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2025)
Abstract: This study aims to identify internship experiences as a means of developing hard and soft skills competencies among students of the Agribusiness of Agricultural Product Processing (APHP) expertise program at SMK Baitul Izza. This study employs a qualitative approach with a case study design, involving three twelfth-grade APHP students, one internship coordinator, one internship supervising teacher, and one industry mentor as the primary informants. Data were collected through in-depth interviews, observations, and documentation, and were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings show that internship activities contribute to the development of students’ technical competencies (hard skills). Students were able to apply theoretical knowledge acquired at school to industrial practice, master the use of modern tools and materials, and implement occupational health and safety (OHS) principles. In addition, internships also enhance non-technical competencies (soft skills), such as discipline, responsibility, teamwork, interpersonal communication, and adaptability to professional work environments. Overall, internships function as an effective form of contextual learning that bridges the gap between the educational environment and the industrial world. Through direct workplace experience, students not only become more proficient technically but also develop strong work character and readiness to compete in the labor market. Therefore, the implementation of internships at SMK Baitul Izza has proven to make a significant contribution to achieving the goals of vocational education—producing competent, professional, and competitive graduates in the modern industrial era. Keywords: internship, hard skills, soft skills, work competence, vocational education